The Effect of Broken Homes on Self-Esteem among adolescents in Suka Maju Village - Reskiana, Indri; Suwarjo, Suwarjo; Asmen, Faisal (Psikopedagogia, 2021)
The study aims to determine the effect of a broken home family on adolescent self-esteem in Suka Maju Village. Respondents in this study were 36 teenagers from broken homes recruited using the purposive sampling technique. The data were collected using a questionnaire and self-esteem scale and analyzed using simple linear regression. The study found that broken homes significantly affected self-esteem among adolescents in Suka Maju Village. This study can serve as a reference for school counselors in developing the self-esteem of adolescents from broken homes.